Enhanced energy dissipated foams for bicycle helmets - Zheng, John Yizhe (Nanyang Technological University, 2020)
Polyether Block Amide (PEBA) is a high performing thermoplastic elastomer known for its outstanding energy damping properties and this provides a new avenue of development in helmet safety for bicycles. Having the inner foam liner of the helmet to take on a corrugated structure was also proven in previous studies to have tremendous potential in improving the effectiveness of helmets while reducing the overall weight. This final year project seeks to understand the behaviour of different densities of corrugated Expanded Polystyrene (EPS) foam under impact and developing an Acrylonitrile Butadiene Styrene (ABS)-PEBA hybrid-shelled structure in an effort to enhance impact dissipation of the helmets. The baseline comparison study under impact for different configurations is compared with a typical configured ABS-shelled EPS foam samples with no additional design inputs. EPS foam samples are split into 2 categories. Corrugated EPS foam (CF) samples were manufactured for Experiment Set 1, to study the behaviour of different densities while plain EPS foam (PF) samples were manufactured for Experiment set 2 aimed at further understanding the usability of PEBA in bicycle helmets. The foam samples are grouped into 4 density ranges; Group A (50g/L–59g/L), Group B (60g/L–75g/L), Group C (76g/L–90g/L) and Group D (91g/L–105g/L). For Experiment Set 2, ABS shells and PEBA liners were carefully manufactured to different thicknesses to allow for different configurations of the two components. They are grouped into 3 categories based on the thickness of the liner; Group X (0.4mm), Group Y (0.6mm) and Group Z (1.2mm). Once the samples were created, impact tests were performed to determine the effect of foam density and the addition of PEBA liner on the samples’ energy absorption ability. Peak load, peak acceleration and failure mechanisms were also analysed in this project. For Experiment set 1, it can be concluded that CF samples of group C density range exhibit the best results in energy absorption when compared to PF samples while being approximately 30g/L less dense. All samples passed the acceleration criteria of 300G. In Experiment set 2, results garnered from experimental trials have shown that samples with the addition of PEBA liner, exhibit around 5% greater energy absorption during impact. Observable damage to the foams were also less severe for these samples.